Legal Protection for the Community of Wonokerto Village Occupying Village Land Without Legality - Setiawan, Dimas Bakti; Harahap, Nurmalita Ayuningtyas (Candela Edutech Indonesia, 2025)
This study analyzes the use of Kasultanan land as a residence in Wonokerto Village for 63 years without legality. The method used is empirical law with primary and secondary data collection through literature studies, field observations, and interviews with the community, Wonokerto Village Office, and Panitiksmo. The use of Kalurahan land as a residence violates Governor Regulation Number 24 of 2024, but is based on historical aspects where there was a mandate from Sri Sultan Hamengkubuwono IX in 1961 to move the community group from the disaster-prone area of ​​Mount Merapi. This creates a lack of legal certainty for the community group. As a result, the community group cannot carry out legal acts such as Liyer and Lintir. The results of the study show that the Sultanate can release the rights of Anggaduh Kalurahan Wonokerto to become the Sultanate's land, so that the community can submit Serat Kekancingan for legality and be used as legal protection for the community group. Although there are regulations, the resolution refers more to the Sultanate's policy. More explicit and legally binding regulations are needed, such as the Governor's Regulation on resolving the status of village land that has been used by the community as a residence, so that the community can obtain clear legal certainty.